Teaching Materials Developments for Digital Native Students (International Journal of Scientific Research and Management (IJSRM), 2017)
The total quality management had raised the further question about changing in classroom activities. The Further development this idea will determine that human factors take role in total quality management, especially in developing classroom presentation. Thus, this research report is purposed to explain how classroom management influences the students’ behavior in class. Thus, the classroom presentation will more applicable for students, also make the warm discussion, as the total quality management is used in classroom activities. The students have to be active when they are learning in class